Exploring Teachers’ and Students’ Perceptions of AI Tools in Teaching EFL Writing Skill at Vocational School - Bq. Wanda Awalia; Dira Permana; Edi Firman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Artificial intelligence (AI) has increasingly transformed English as a Foreign Language (EFL) writing instruction, particularly in vocational education where students are expected to develop workplace-oriented communication skills. This study aimed to explore teachers’ and students’ perceptions of AI tools in teaching EFL writing at a tourism-focused vocational school. Employing a qualitative descriptive design, the study involved three English teachers and fifteen eleventh-grade students of SMKN 1 Batulayar. Data were collected through semi-structured interviews, classroom observations, and document analysis of students’ writing products. The data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing, while triangulation was employed to ensure trustworthiness. The findings revealed that teachers generally perceived AI as a beneficial instructional support tool that facilitates grammar checking, feedback provision, and material preparation. However, they expressed concerns regarding students’ dependence on AI, declining vocabulary retention, reduced critical thinking, and diminished writing originality. Students, on the other hand, viewed AI as a practical and efficient tool for generating ideas, improving grammar, translating vocabulary, and completing writing assignments. Despite these benefits, many students reported feelings of guilt, lack of confidence, and reduced independence in composing texts. Classroom observations and document analysis further demonstrated a discrepancy between students’ submitted writing products and their actual language competence. The study concludes that AI possesses significant pedagogical potential when utilized as a learning scaffold rather than a substitute for students’ cognitive efforts. Therefore, AI integration in EFL writing instruction should be accompanied by AI literacy education, process-based assessment, ethical guidelines, and teacher-mediated feedback. These measures are essential to ensure that AI supports students’ writing development while maintaining their critical thinking, language competence, and professional readiness.